Anti-cryptococcal activity of ethanol crude extract and hexane fraction from Ocimum basilicum var. Maria bonita: mechanisms of action and synergism with amphotericin B and Ocimum basilicum essential oil - Nathalia N. R. Cardoso; Celuta S. Alviano; Arie F. Blank; Maria de Fátima Arrigoni-Blank; Maria Teresa V. Romanos; Marcel M. L. Cunha; Antonio Jorge R. da Silva; Daniela S. Alviano (Taylor & Francis Group, 2017)
Context: Ocimum basilicum L. (Lamiaceae) has been used in folk medicine to treat headaches, kidney disorders, and intestinal worms. Objective: This study evaluates the anti-cryptococcal activity of ethanol crude extract and hexane fraction obtained from O. basilicum var. Maria Bonita leaves. Materials and methods: The MIC values for Cryptococcus sp. were obtained according to Clinical and Laboratory Standards Institute in a range of 0.3-2500 μg/mL. The checkerboard assay evaluated the association of the substances tested (in a range of 0.099-2500 μg/mL) with amphotericin B and O. basilicum essential oil for 48 h. The ethanol extract, hexane fraction and associations in a range of 0.3-2500 μg/mL were tested for pigmentation inhibition after 7 days of treatment. The inhibition of ergosterol synthesis and reduction of capsule size were evaluated after the treatment with ethanol extract (312 μg/mL), hexane fraction (78 μg/mL) and the combinations of essential oil + ethanol extract (78 μg/mL + 19.5 μg/mL, respectively) and essential oil + hexane fraction (39.36 μg/mL + 10 μg/mL, respectively) for 24 and 48 h, respectively. Results: The hexane fraction presented better results than the ethanol extract, with a low MIC (156 μg/mL against C. neoformans T444 and 312 μg/mL against C. neoformans H99 serotype A and C. gattii WM779 serotype C). The combination of the ethanol extract and hexane fraction with amphotericin B and essential oil enhanced their antifungal activity, reducing the concentration of each substance needed to kill 100% of the inoculum. The substances tested were able to reduce the pigmentation, capsule size and ergosterol synthesis, which suggest they have important mechanisms of action. Conclusions: These results provide further support for the use of ethanol extracts of O. basilicum as a potential source of antifungal agents.